S-BPM in the Production Industry: A Stakeholder Approach - Neubauer, Matthias; Stary, Christian (SpringerLink, 2017)
This book is open access under a CC BY-NC 4.0 license.This volume presents several case studies highlighting the latest findings in Industry 4.0 projects utilizing S-BPM features.Their potential is explored in detail, while the limits of engineering a company from a communication-centred perspective are also discussed.